Exploratory study on visual merchandising in Singapore. - Lim, Jing Pei. (2008)
The main aim of this study was to explore the consumers' perception of visual merchandising in Singapore. A qualitative approach was adopted, and conclusions were drawn from a focus group and semi-structured interviews with respondents.